1980
DOI: 10.1097/00006842-198011000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response to Touch1

Abstract: The effect of tactile stimulation on heart rate (HR) in humans was investigated under three conditions: 1) Experimenter outside of room in which subject is sitting; 2) experimenter in the room with the subject; 3) experimenter in the room while touching the subject's right wrist. Nonsignificant increases in HR were observed when the experimenter entered the room (X = 0.64 beats per minute (bpm)). Conversely, large decreases occurred when the experimenter placed his hand on the subject's wrist (X = 9.16 bpm, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…In both of our subjects, heart rate deceleration was more dramatic while receiving grooming than in matched control periods. Interestingly, heart rate effects that are similar to those of allogrooming have also been found for petting or gentle touching by human experimenters in horses, rhesus macaques, and humans (Drescher, Gantt, & Whitehead, 1980;Drescher, Hayhurst, Whitehead, & Joseph, 1982;Feh & De Mazieres, 1993).…”
Section: Allogrooming and Tension Reductionmentioning
confidence: 82%
“…In both of our subjects, heart rate deceleration was more dramatic while receiving grooming than in matched control periods. Interestingly, heart rate effects that are similar to those of allogrooming have also been found for petting or gentle touching by human experimenters in horses, rhesus macaques, and humans (Drescher, Gantt, & Whitehead, 1980;Drescher, Hayhurst, Whitehead, & Joseph, 1982;Feh & De Mazieres, 1993).…”
Section: Allogrooming and Tension Reductionmentioning
confidence: 82%
“…Some literature namely suggests that relatively extensive touching actions such as hugs or massages (contact area) or holding hands (duration) can decrease (physiological) stress responses (e.g., Grewen et al, 2003;Coan et al, 2006;Ditzen et al, 2007). On the other hand, it is claimed that briefly touching one's arm, or providing a supportive pat on the back (e.g., Whitcher and Fisher, 1979;Drescher et al, 1980) can already decrease stress. The duration and contact area may thus influence the responses to a human touch, but the underlying mechanisms are not yet fully understood (Field, 2010;van Erp and Toet, 2015).…”
Section: Stress Responses and Stimuli Aversion (H1 And H2)mentioning
confidence: 99%
“…This indicates the direct link between skin stimulation and physiological processes, a link that is preserved later in life. For instance, gentle stroking touch can lower heart rate and blood pressure (Grewen et al 2003), increase transient sympathetic reflexes and increase pain thresholds (Drescher et al 1980;Uvnäs-Moberg 1997), and affect the secretion of stress hormones (Whitcher and Fisher 1979;Shermer 2004;Ditzen et al 2007). Women holding their partner's hand showed attenuated threat-related brain activity in response to mild electric shocks (Coan et al 2006) and reported less pain in a cold pressor task (Master et al 2009).…”
Section: Touch In Social Communicationmentioning
confidence: 99%